Kontribusi Kemampuan Awal Dan Aktivitas Belajar Terhadap Kesulitan Belajar Mata Kuliah Akuntansi Keuangan Menengah 1 Pada Mahasiswa Pendidikan Akuntansi Angkatan 2014 Universitas Muhammadiyah Surakarta - DIAH UTAMI, FATIMAH; , Drs. Budi Sutrisno, M.Pd (2016)
The purpose of this study was determine: 1)Contributions of prior knowledge to learning difficulty courses Financial Accounting based on Medium 1, 2) Contributions learning activities to learning difficulty courses Financial Accounting based on Medium 1, 3) Contributions of prior knowledge and learning activities to learning difficulty courses Financial Accounting based on Medium 1. This study is quantitative descriptive research whose conclusions obtained based on the results of statistical analysis. This study took place in the Campus 1 Muhammadiyah University of Surakarta. The population in this study were all students of UniversitasMuhammadiyah Surakarta Accounting Education Force 2014/2015 taking courses in Financial Accounting based on Medium1 totaling 235 students with a sample of 142 students were taken by proportional random sampling technique in a random way. The necessary data and documentation obtained through a questionnaire that has previously been tested by validity and reliabiliatas. Data analysis technique used is multiple linear regression t-test, F, R2 test, and the relative contribution and effective. The results using regression analysis regression equation: Y = 7,486 + 0,575X1 + 0,353X2. The research found that: 1) There is a positive and significant contributionof prior knowledge to learning difficulty courses Financial Accounting based on Medium 10.575 evidenced by the regression coefficient is positive and obtained t >t table is 10,605 > 1,977and the significance value <0.05 is 0,000; 2) There is a significant positive contribution learning activities to learning difficulty courses Financial Accounting based on Medium 10.353 evidenced by the regression coefficient is positive and obtained t >t table is 6,396 > 1,977and the significance value <0.05 is 0,000; 3) There is a significant and positive contribution of prior knowledge and learning activities to learning difficulty courses Financial Accounting based on Medium 1 proven results obtained F>Ftable is 123,832 > 3,061and the value of 0.05 is 0,000; 4) the coefficient of determination (R2) obtained 0,641indicates that learning difficulty courses Financial Accounting based on Medium 1are affected byprior knowledge and learning activities at64,1% comprising 43,2% prior knowledge and 20.9% of learning activities and the remaining 35,9% is influenced by other variables not examined.